2006
DOI: 10.1111/j.1471-0528.2006.01090.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow‐mediated dilatation in overweight and obese women with polycystic ovary syndrome

Abstract: Objective There remains a large degree of disagreement about the association of polycystic ovary syndrome (PCOS) with impaired endothelial dysfunction and cardiovascular disease (CVD) risk. The purpose of this study was to determine whether overweight and obese women with PCOS have impaired endothelial function compared with weight-matched controls without PCOS and whether endothelial function is associated with cardiovascular risk markers and hormonal parameters.Design Cross-sectional analysis. Setting An out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 66 publications
4
24
1
3
Order By: Relevance
“…Consistent with our results, most of the studies, but not all [8,12], demonstrated impaired endothelial function in PCOS using either noninvasive endothelium-dependent (FMD) and-independent (glyceroltrinitrate, GTN) changes in the brachial artery or invasive methodology [4,6,10,11,24] compared with the controls. Among several circulating endothelium-derived vasoactive molecules, ET-1 is considered one of the best indices of abnormal vascular reactivity, playing an important role in the early events of endothelial dysfunction [4].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Consistent with our results, most of the studies, but not all [8,12], demonstrated impaired endothelial function in PCOS using either noninvasive endothelium-dependent (FMD) and-independent (glyceroltrinitrate, GTN) changes in the brachial artery or invasive methodology [4,6,10,11,24] compared with the controls. Among several circulating endothelium-derived vasoactive molecules, ET-1 is considered one of the best indices of abnormal vascular reactivity, playing an important role in the early events of endothelial dysfunction [4].…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, we might speculate that some genetic abnormalities, such as polymorphisms in AR or other yet unidentified genetic abnormalities aggravated by the higher levels of androgens found in PCOS subjects, may be responsible for impaired endothelial function observed in our test group in comparison with our control group. Several lines of evidence, but not all [8,10,12,27,33], revealed an association between insulin resistance and endothelial dysfunction markers in PCOS women [4,7,9,11,34]. We observed however, significant correlations of FMD with insulin concentrations and HOMA-IR, but only in the entire population studied.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…The mean FMDs of the brachial artery of both groups were assessed by a non-invasive method previously used by Brinkworth and et al [16] in their study. Doppler US examinations were performed with a 10 mHz linear array transducer and a Logiq 9 US system (GE Medical Systems, Milwaukee, Wisconsin, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, women with PCOS display signs of endothelial dysfunction, which is an early event in the development of atherosclerosis that precedes plaque formation and clinical disease. Endothelial function is evaluated in PCOS patients, mostly by measuring post-ischemic flow mediated dilatation of the brachial artery by high-resolution ultrasonography and by measuring arterial stiffness with pulse wave velocity [83][84][85][86][87][88][89]. Women with PCOS also display signs of sub-clinical atherosclerosis at young age [13, 76-78, 86, 90-92].…”
Section: Cardiovascular Consequences Of Pcosmentioning
confidence: 99%